Zastosowanie Metod Lokalnego Odprężania do Określania Naprężeń w Tubingach Żeliwnych - Dyląg, Z. (Engineering Transactions, 1964)
The present paper is devoted to some selected methods for determining the residual stresses, most suitable for the problem under consideration. A number of methods of representing the results are proposed as well as a measurement method for solving the problem that is for determining, in a possibly simple and inexpensive way, the value of the residual stresses at certain points of cast iron tubings. The control tests carried out by the author are described, giving a discussion of the results. A number of diagrams are given, which can be of use for similar investigations. In conclusion, a number of practical remarks are given, concerning the above methods.